The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsnanoscienceau.1c00028
|View full text |Cite
|
Sign up to set email alerts
|

Co-Doping of Cerium and Bismuth into Lead-Free Double Perovskite Cs2AgInCl6 Nanocrystals Results in Improved Photoluminescence Efficiency

Abstract: Lead-free double cation metal halide perovskites have recently attracted considerable attention, with continuing research efforts focusing on the improvement of their stability and photoluminescence quantum yield (PL QY). In this study, Ce3+ has been co-doped together with Bi3+ into lead-free double perovskite Cs2AgInCl6 nanocrystals (NCs) in order to improve their crystallinity and PL QY. Both uncoordinated chloride ions and silver vacancies could be eliminated using this co-doping strategy, and the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…While based on the hot-injection procedure, multiple efforts have been made throughout the following years to enhance the stability and boost the PL QY of perovskite NCs. Doping/alloying to inhibit the nonradiative pathways, surface treatments for effective passivation of defects, proper choice of ligands, and dimensionality engineering have all been applied. Besides, strategies are appearing now aimed at reducing or eliminating the amount of lead in perovskite NCs through its partial or complete substitution, which led to the development of A 2 M + M 3+ X 6 lead-free double perovskites. …”
Section: Introductionmentioning
confidence: 99%
“…While based on the hot-injection procedure, multiple efforts have been made throughout the following years to enhance the stability and boost the PL QY of perovskite NCs. Doping/alloying to inhibit the nonradiative pathways, surface treatments for effective passivation of defects, proper choice of ligands, and dimensionality engineering have all been applied. Besides, strategies are appearing now aimed at reducing or eliminating the amount of lead in perovskite NCs through its partial or complete substitution, which led to the development of A 2 M + M 3+ X 6 lead-free double perovskites. …”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] However, the effect of bismuth dopants on In-based halide perovskites (represented by Cs 2 AgInCl 6 perovskites) has been extensively studied in the field of all-inorganic perovskites. In these studies, by adjusting the optical bandgap, 23 breaking the parity forbidden transition, 24 promoting light absorption and introducing an energy transmission channel, [25][26][27] Bi 3+ has been shown to play a role in photoluminescence (PL), which is different from the luminescent center Sb 3+ . Shi et al recently reported that when Sb 3+ and Bi 3+ ions were co-doped into the Cs 2 NaInCl 6 double perovskite, the Bi 3+ dopants induced [SbCl 6 ] 3À octahedral subbands and enhanced the broadband yellow radiation of selftrapped excitons (STEs) in the [SbCl 6 ] 3À octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in these low-D NCs, apart from a few examples, [129] doping strategies have not been yet fully exploited. For example, the co-doping with two metal cations for tunable light emission, which has been successfully exploited in both 3D CsPbX 3 [130] and double perovskite NCs, [131] has been demonstrated only in Cs 2 ZrCl 6 microcrystals, but not in NCs. [132,133] Therefore we believe that an interesting research direction will be the development of effective doping strategies of low-D NCs.…”
Section: Discussionmentioning
confidence: 99%